Influence of Green Supply Chain Management Practices on Organization Performance: An Interpretive Structural Modeling Approach - Gupta, Mamta; Sarita Chaudhary (Lembaga Penerbit Fakultas Ekonomi dan Bisns, Universitas Trisakti, 2026)
This study examines the role of digital technologies in enhancing green supply chain performance and environmental sustainability across industrial sectors. As firms increasingly prioritize environmental responsibility, digitalization has emerged as a critical enabler of efficient and sustainable supply chain practices. This research focuses on five key digital technologies—Big Data, Cloud Computing, Blockchain, the Internet of Things, and Artificial Intelligence—and evaluates their impact on green supply chain initiatives.Using a quantitative approach, the study employs causal modeling and hypothesis testing to analyze the relationships between digital technology adoption and environmental performance outcomes. Data were collected from 114 respondents representing small-, medium-, and large-sized enterprises across diverse industries, including automotive, textiles, paper, chemical, and steel sectors. The findings indicate that the adoption of digital technologies significantly contributes to improved green supply chain performance by enhancing operational efficiency, optimizing resource utilization, reducing energy consumption, and mitigating emissions. The results highlight the strategic importance of integrating advanced digital solutions into supply chain processes to achieve broader economic, environmental, and social benefits. This study provides empirical evidence supporting the role of digital transformation in driving sustainable supply chain practices and offers practical insights for managers and policymakers seeking to promote environmentally responsible industrial development.